The marginal utility of money: A modern Marshallian approach to consumer choice - Daniel Friedman; József Sákovics (University of California, Economics Department, 2011)
We reformulate neoclassical consumer choice by focusing on [lambda], the marginal utility of money. As the opportunity cost of current expenditure, [lambda] is approximated by the slope of the indirect utility function of the continuation. We argue that [lambda] can largely supplant the role of an arbitrary budget constraint in partial equilibrium analysis. The result is a better grounded, more exible and more intuitive approach to consumer choice.
Keywords: D01; D03; D11; 330; budget constraint; separability; value for money